Survey Data of Water Bioremediation by Microalgae Botryococcus sp. at Taman Dagang Jaya, Selangor - Apandi, Najeeha (Progress in Engineering Application and Technology, 2021)
This paper presents data collected from a survey on the bioremediational water treatment using immobilized microalgae. This study is aimed to evaluate and investigate the knowledge of the respondents at a residential area on the level of knowledge and the acceptance rate on the bioremediation process as water treatment. The data of 50 respondents representing 77.6% of the respondent would recommended this study to others and 62% would switch to this process due to cost effective and environmental friendly. The results also indicated that 57% of the respondent had no information and knowledge about bioremediation that already being conducted globally. The data are provided in a way to establish design criteria for futher experiment in water treatment using immobillized microalgae at residential community.